The Relevance of Words and Meaning in Students’ Infographics Based on Sperber & Wilson - Andayani, Wuwuh; Zainal Rafli; Fathiaty Murtadho (Institut Agama Islam Negeri Palopo, 2024)
The use of relevant and concise wording in infographics is crucial to ensure that the information presented can be quickly and effectively understood by readers. However, existing infographics still need to strike a balance between information density and clarity of delivery. This study explores the relevance of words and meaning in student-created infographics, using Sperber & Wilson’s Relevance Theory (1986, 1995) as a framework. By analyzing three student-created infographics, the study identified the main structural elements of infographics: description (general overview), details (specific information), and significance (practical value). It also examined audience intentions, categorized as either informative or communicative. The results revealed that the